Способ измерения тока с помощью двух герконов - Горюнов В. Н. Владимир Николаевич; Жалмагамбетова У. К.; Жантлесова А. Б. Асемгуль Бейсембаевна; Клецель М. Я. Марк Яковлевич
опубл. 15.11.11, Бюл. № 11